The Asset of Subjectivity: Applying Mujerista Theology and Family Interest Assessment to Case Analysis - Hood-Patterson, Rebecca (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Applying two theories to complex contexts results in a more well-rounded case analysis. This case, involving a Latinx family within pediatrics, requires a multi-faceted approach to better evaluate the culturally specific needs of the patient and the family system. A Mujerista theological approach highlights the subjective nature of family values and lived wisdom. This Mujerista approach adds another dimension, along with a Family Interest Model, for medical decision making.